Manajemen Perubahan SMK di Kabupaten Pacitan - Luqman Hadi (Transformasi : Jurnal Studi Agama Islam, 2020)
This article is intended to describe the management of change by the principal as a manager in quality improvement change. Research conducted using qualitative with ethnographic design. Data analysis includes: domain analysis, taxonomic analysis, and compound analysis. The results of the analysis show that change management in the planning, organizing, mobilizing, controlling, and evaluating processes is the main task / responsibility of the school principal's deputy in the transportation team. The strategy used is empirical rational and the division of power with the policy being carried out is the development of teacher professionalism. Values that are believed to be the success of change are the discipline of teacher and student, teacher and student motivation, teacher and student commitment, and academic culture that improves.